Aspiration Versus Stent‐Retriever as First‐Line Endovascular Therapy Technique for Primary Medium and Distal Intracranial Occlusions: A Propensity‐Score Matched Multicenter Analysis - Siegler, James E.; Shaikh, Hamza; Khalife, Jane; Oak, Solomon; Zhang, Linda; Abdalkader, Mohamad; Klein, Piers; Nguyen, Thanh N.; Kass‐Hout, Tareq; Morsi, Rami Z.; Heit, Jeremy J.; Regenhardt, Robert W.; et al. (Stroke: vascular and interventional neurology, 2023)
BackgroundFor acute proximal intracranial artery occlusions, contact aspiration may be more effective than stent‐retriever for first‐line reperfusion therapy. Due to the lack of data regarding medium vessel occlusion thrombectomy, we evaluated outcomes according to first‐line technique in a large, multicenter registry.MethodsImaging, procedural, and clinical outcomes of patients with acute proximal medium vessel occlusions (M2, A1, or P1) or distal medium vessel occlusions (M3, A2, P2, or further) treated at 37 sites in 10 countries were analyzed according to first‐line endovascular technique (stent‐retriever versus aspiration). Multivariable logistic regression and propensity‐score matching were used to estimate the odds of the primary outcome, expanded Thrombolysis in Cerebral Infarction score of 2b–3 (“successful recanalization”), as well as secondary outcomes (first‐pass effect, expanded Thrombolysis in Cerebral Infarction 2c‐3, intracerebral hemorrhage, and 90‐day modified Rankin scale, 90‐day mortality) between treatment groups.ResultsOf the 440 included patients (44.5% stent‐retriever versus 55.5% aspiration), those treated with stent‐retriever had lower baseline Alberta Stroke Program Early Computed Tomography Scale scores (median 8 versus 9; P<0.01), higher National Institutes of Health Stroke Scale scores (median 13 versus 11; P=0.02), and nonsignificantly fewer medium‐distal occlusions (M3, A2, P2, or other: 17.4% versus 23.8%; P=0.10). Use of a stent‐retriever was associated with 15% lower odds of successful recanalization (odds ratio [OR], 0.85; [95% CI 0.74–0.98]; P=0.02), but this was not significant after multivariable adjustment in the total cohort (adjusted OR, 0.88; [95% CI 0.72–1.09]; P=0.24), or in the propensity‐score matched cohort (n=105 in each group) (adjusted OR, 0.94; [95% CI 0.75–1.18]; P=0.60). There was no significant association between technique and secondary outcomes in the propensity‐score matched adjusted models.ConclusionIn this large, diverse, multinational medium vessel occlusion cohort, we found no significant difference in imaging or clinical outcomes with aspiration versus stent‐retriever thrombectomy.